Feasibility of cytological diagnosis of sarcoidosis with endobronchial US-guided transbronchial aspiration - Kitamura, A.; Takiguchi, Y.; Kurosu, et al., K. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2012)
Background: Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) has a high diagnostic value in sarcoidosis if the obtained histological specimen is indicative of a non-caseating epithelioid-cell granuloma. However, EBUS-TBNA in sacoidosis sometimes affords solely cytological specimens. Objective: To investigate the relevance of EBUS-TBNA cytology specimens in diagnosing sarcoidosis. Design: The study population comprised 72 patients with sarcoidosis and 116 patients who had thoracic malignancies and intrathoracic lymphadenopathy but were eventually proven to be metastasis-free (controls). The EBUSTBNA samples obtained for these subjects were blindly evaluated for the presence of epithelioid cell clusters by 2 independent cytoscreeners and a pathologist. Results: Interobserver variability in the specimen grading was minimal. The sensitivity and specificity were 65.3% and 94.0%, respectively. The sensitivity was high, at 87.5%, for the combined cytological and histological examinations. Of 7 controls whose cytological specimens showed epithelioid cell clusters, 3 were also deemed positive for sarcoidosis on histological examination, which indicated that they had sarcoid reaction to cancer. Conclusions: Cytological evaluation of the EBUS-TBNA specimens had higher sensitivity than histological evaluation alone for intrathoracic lymphadenopathy due to sarcoidosis. It should be recognized, however, that up to 6% of patients with thoracic malignancy may have sarcoid reaction in non-metastatic lymph nodes.